PERSPEKTIF BARAKAH DALAM KESARJANAAN MUSLIM BARAT: STUDI ATAS PEMIKIRAN NAOUMAN ALI KHAN DI YOUTUBE - lia Qurrota Aini (Universitas Nurul Jadid, 2020)
Barokah has been around for a long time even though it does not appear to be about its form, but everyone must feel the sweetness of barokah. The problem is that barokah has experienced a decline and has even begun to become extinct because its existence is not clearly visible. That is caused by the lack of public awareness of the power of Allah, so that it depends on the progress of science and technology at this time. Therefore, the author examines the interpretation of Nouman Ali Khan through Youtobe which contains a discussion of baraka as a form of recommendation to the public that the interpreter is very suitable to be studied at the present time. This article includes thematic methods (maudhu'i) as well as patterns of adab ijtima'i with a linguistic approach, so that the discussion presented by Nouman Ali Khan can be used as a basis for knowing, understanding and changing the paradigm of society through cognitive effects, affective effects, and behavioral effects.